One piece. Collection no. 19. [videorecording (DVD)] - Miyamoto, Hiroaki; Glass, Caitlin, 1981-; Oda, Eiichirō, 1975- (FUNimation, 2017)
The Straw Hat Pirates share adventures in their search for a mysterious treasure called the One Piece.